ETIMOLOGI SAUJANA SEBAGAI CULTURAL LANDSCAPE - Salouw, Elvis; Ikaputra, Ikaputra (Jurnal Arsitektur ARCADE, 2022)
Abstract: The term Landscape has different meanings from various points of view. Landscape in the scope of planning is defined as the aesthetics of the scenery, the urban environment, the field of land cover related to visuals as well as areas related to traditional and cultural characteristics. Cultural landscape is a landscape that is formed as a result of human interaction with nature. In Indonesia, the cultural landscape is defined as Saujana. The use of the word saujana in various studies related to landscape has not been completely consistent. By using the literature study method, this study aims to examine the etymology of Saujana and its suitability with the terminology of the cultural landscape. The results of this study found that the word saujana has the closest meaning to the word Landscape, but it is not appropriate when it is paired with the term cultural landscape. The recommendation from this study is that the use of the term saujana which refers to the cultural landscape needs to be reviewedAbstrak: Istilah Landscape memiliki pemaknaan yang berbeda dari berbagai sudut pandang. Landscape dalam lingkup perencanaan diartikan sebagai sebagai estetika pemandangan, lingkungan perkotaan, bidang tutupan lahan yang berkaitan dengan visual serta area yang berkaitan dengan karakteristik adat dan budaya. Cultural landscape merupakan landscape yang terbentuk dari hasil interaksi manusia dengan alam. Di Indonesia, cultural landscape diartikan sebagai Saujana. Pengunaan kata saujana dalam berbagai penelitian yang berkaitan dengan landscape belum sepenuhnya konsisten. Dengan menggunakan metode studi kepustakaan, penelitian ini bertujuan untuk mengkaji etimologi saujana serta kesesuaiannya dengan terminologi cultural landscape. Hasil penelitian ini memberikan gambaran bahwa kata saujana memiliki kedekatan makna dengan kata landscape, namun tidak sesuai jika dipadankan dengan istilah cultural landscape. Rekomendasi dari studi ini adalah penggunaan istilah saujana yang merujuk pada cultural landscape perlu dikaji kembali.